As organizações religiosas centenárias no Ipiranga - São Paulo SP: lacunas na relação com a Política de Assistência Social - Leão, Paula Silva (2024)
This thesis is the result of research that sought to investigate centuries-old organizations in the Ipiranga territory in the city of São Paulo that offer social assistance services. It brings the history of the territory with the understanding that it is the result of human relations and conflicts between capital and work. The thesis presents the particularity of Catholic social action in the city of São Paulo initiated by the brotherhoods, as well as the history of this offer from its constitution by the centuries-old Catholic social organizations investigated: the Instituto Cristóvão Colombo and the Fundação Nossa Senhora Auxiliadora. It sought to understand how the relationship between social care provided by social organizations and municipal social assistance policy occurs, identifying existing gaps. This reflection reveals the specificities of the working conditions existing in social assistance organizations that express different levels of inequality among workers in the Unified Social Assistance System and how this work affects the quality of services. The methodology used was qualitative, based on bibliographical and documentary research and six oral interviews, which were selected based on the following criteria: organizations that operate in the Ipiranga territory; organizations without a partnership or development agreement with public authorities, that is, without funding from the Municipal Secretariat for Social Assistance and Development (SMADS); organizations that had orphanages; Catholic orientation in its activities; organizations with more than a hundred years of foundation and continued activity. Based on these criteria, we interviewed a manager, a service coordinator and a social worker. The results of this thesis indicate that there are gaps, tensions and disputes in the relations between the State and CSOs. It is advocated the establishment of rules that support an effective partnership relationship between entities recognized as providing social assistance and the guarantee of protections under the responsibility of the National Social Assistance Policy (PNAS), to ensure comprehensive care for users of social assistance services